High number of seizures and unconsciousness in patients with SARS-CoV-2 omicron variants: a retrospective study - Tokuyama, Kishin; Kitamura, Tsubasa; Maruyama, Kazutaka; Toriumi, Shun; Murano, Yayoi; Yoneoka, Daisuke; Nakazawa, Tomoyuki; Shimizu, Toshiaki (Frontiers in Pediatrics, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron variants are now a pandemic. There are differences in clinical features in SARS-CoV-2 variants and we conducted this study to assess the clinical features of coronavirus disease (COVID-19) in children with SARS-CoV-2 omicron variants. The study included children with COVID-19 arrivedadmitted to Tokyo Metropolitan Toshima Hospital between January 2020 and October 2022. The clinical features of 214 children with SARS-CoV-2 non-omicron variants and 557 children with omicron variants were compared. In the SARS-CoV-2 omicron variant group, more patients had fever, sore throat, nausea and/or vomiting, and seizures and/or disorders of consciousness. In SARS-CoV-2 non-omicron variants, there was only one patient with seizure and/or unconsciousness whereas there were 92 children in omicron variants. Among these 92 patients, 46 (49%) were diagnosed with simple febrile seizures; 23 (25%), with complex febrile seizures; 10 (11%) with status epilepticus; and two (2%) with encephalopathy. Their mean age was 4.0 ± 3.0 years-a wider age distribution than that in other febrile seizures but similar to that in febrile seizures in patients with influenza. SARS-CoV-2 omicron variants are likely to cause seizures and unconsciousness in children and their age distribution was wider than other febrile seizures patients but similar to those in influenza patients. In clinical practice in patients with COVID-19 and influenza, clinicians should be aware of these features.